Understanding inequality the intersection of race/ethnicity, class, and gender - edited by Barbara A. Arrighi (Lanham Rowman & Littlefield Publishers, 2007)
As the age of globalization and New Media unite disparate groups of people in new ways, the continual transformation and interconnections between ethnicity, class, and gender become increasingly complex. This reader, comprised of a diverse array of sources ranging from the New York Times to the journals of leading research universities, explores these issues as systems of stratification that work to reinforce one another. Understanding Inequality provides students and academics with the basic hermeneutics for considering new thought on ethnicity, class, and gender in the 21st century.
Includes bibliographical references and index.
Keywords: Equality -- United States; Minorities -- United States -- Social conditions; Social classes -- United States; Sex role -- United States; United States -- Social conditions